Reconstruction of an Anal Sphyncter Which had suffered Extensive Destruction of the Recto - Vaginal Wall - Torterolo, Edgardo; Bermúdez, Jorge (Cirugía del Uruguay, 1981)
The patient had been operated severa! times in attempts to repair anal sphyncter and perineum, secondary to abscess and fistula, which had failed. An iliac colostomy was first performed, then the perineum and sphyncter were repaired in an anatomic manner, with excellent functional result. There follows an account of certain aspects of this technique and surgical tactics which are essential to success.